Constitutional Court as Positive The Constitutional Court as Positive Legislator: Rethinking Checks and Balances Considering Decision No. 60/PUU-XXII/2024 - Imelda Ayu Juwita Putri; Bachrul Amiq; Anastasia Kayla Ruwiyanto (Universitas Negeri Surabaya, 2026)
This study analysed the evolving role of the Constitutional Court in Decision Number 60/PUU-XXII/2024, which not only annuls legal norms but also establishes new norms regarding regional head candidacy requirements. This condition raises debates concerning the shift of the Constitutional Court's function from a negative legislator to a positive legislator and its implications for the principle of checks and balances within Indonesia's constitutional system. Unlike prior studies, which have remained largely conceptual or focused on the technical implementation of regional elections, this research offers novelty through a critical analysis of the constitutional legitimacy of the Constitutional Court's role in formulating new norms, examined specifically through the lens of checks and balances an angle that remains underexplored in the existing literature. This research aims to analyze the juridical construction of the decision and examine its impact on the balance of power among state institutions. The research employs a normative legal method using statutory, case, and conceptual approaches. The legal materials consist of primary sources, such as legislation and Constitutional Court decisions, and secondary sources, including legal literature and scholarly doctrines, analyzed prescriptively to assess the decision's conformity with the principles of constitutional supremacy and the separation of powers. The findings indicate that Decision Number 60/PUU-XXII/2024 reflects the Constitutional Court's tendency to act as a positive legislator by formulating new candidacy threshold norms a move that, while contributing to democratization, also poses risks of legal uncertainty and a shifting balance of power. These findings reinforce the theoretical argument that the transformation of the Constitutional Court's role necessitates a reformulation of the constitutional limits on judicial authority within a checks-and-balances framework, while opening avenues for strengthening constitutional dialogue between the judiciary and the legislature in Indonesia.